The Microbiology of Complicated Acute Sinusitis among Pediatric Patients: A Case Series. (April 2019) - Mulvey, Carolyn L.; Kiell, Eleanor P.; Rizzi, Mark D.; Buzi, Adva
Objective: The microbiology of pediatric complicated acute rhinosinusitis (ARS) has evolved, and our current understanding of pathogenic organisms is limited. The objectives of this study are to describe the incidence of pathogens causing complicated ARS requiring surgical intervention at our institution over a 10-year period as well as their associated treatment outcomes. Study Design: Retrospective cohort study. Setting: A single tertiary care children's hospital. Subjects and Methods: Data were reviewed from all patients who underwent surgery for complicated ARS and had positive culture data from 2006 to 2016. Associations among pathogens, complications, and outcomes were analyzed with Pearson χ 2 and Wilcoxon rank-sum tests. Results: Eighty-nine patients met criteria. Complications included orbital infections (78%), intracranial infections (48%), Pott's puffy tumor (13%), and cavernous sinus thrombosis (9.0%). Bacterial isolates were majority polymicrobial (55%) and included Streptococcus species (58%), Staphylococcus species (49%; including methicillin-resistant S aureus [MRSA], 11%), and anaerobic bacteria (35%). S pneumoniae (9.0%), Haemophilus species (4.5%), and Moraxella catarrhalis (1.1%) were relatively uncommon. Bacterial isolates were similar among patients with all types of complications. Conclusion: Among a large cohort of pediatric patients with complicated ARS, most bacterial isolates were polymicrobial, with Streptococcus and Staphylococcus species contributing to the majority of cases. S aureus species, including MRSA and anaerobic pathogens, were common. The pattern of bacterial isolates was similar among patients with all types of complications of ARS. We suggest treatment for complicated ARS with broad-spectrum antibiotics with coverage for Streptococcus species, Staphylococcus species including MRSA, and anaerobic bacteria.